Self-Efficacy and Psychological Well-Being in Adolescents: Evaluating the Moderating Role of Socioeconomic Status and Cultural Factors - Giulia Raimondi; James Dawe; Fabio Alivernini; Sara Manganelli; Pierluigi Diotaiuti; Laura Mandolesi; Michele Zacchilli; Fabio Lucidi; Elisa Cavicchiolo (Pediatric Reports)
Background/Objectives: Adolescence is a crucial developmental stage characterized by significant psychological and emotional changes. Within the school context, academic self-efficacy (ASE) influences students’ emotional well-being, including positive and negative affective states. Research has shown that both ASE and emotional well-being are associated with socioeconomic status (SES) and immigrant background. This study aims to examine whether SES and immigrant background moderate the relationship between ASE and positive/negative affect among adolescents. Methods: Data were collected from a representative sample of 26,564 10th-grade students in Italian schools. ASE, positive and negative affect, SES, and immigrant background were assessed through validated measures. Multigroup structural equation modeling (multigroup SEM) was conducted to test the moderating roles of SES (low, middle, high) and immigrant background (native, first-generation immigrant, second-generation immigrant) on the relationship between ASE and affective states. Results: The results indicated that ASE significantly predicted positive affect (β = 0.34, p < 0.001) and negative affect (β = −0.17, p < 0.001) across all groups. However, results indicated no significant differences in the ASE–emotional affect relationship across SES and immigrant background groups, indicating that neither SES nor immigrant background moderated these associations. Conclusions: The findings suggest that ASE is associated with both positive affect and negative affect in adolescents, irrespective of SES and immigrant background. This highlights the universal importance of fostering ASE in school settings to support emotional well-being across diverse demographic groups.